The Role of Independent Commisioners in Moderating the Effect of Profitability, Company Size and Company Risk on Tax Avoidance - Asih, Kurnia Laras; Darmawati, Deni (Asia Pacific Fraud Journal, 2022)
The purpose of this study was to determine and analyze the the role of Independent Commissioners in moderating the effect of profitability, company size, and company risk on tax avoidance in manufacturing companies on the Indonesia Stock Exchange period 2016-2018 with a total of 77 companies. The sampling technique in this study used a purposive sampling technique with a total observation are of 231 firm-years. With multiple regression analysis, this research showed that the Company’s Profitability and Risk had a significant positive effect on Tax Avoidance, while Company Size did not have a significant effect on Tax Avoidance. The Independent Commissioners succeeded in weakening the positive influence of profitability and company risk on tax avoidance.This research succeeds in proving that as a component of the corporate governance mechanism, the Independent Commissioner has a role in supervising managerial decisions, including tax decision.